Produrre spreco. Usi e consumi dell’abbondanza postindustriale - Moccagatta, Vittoria (Filosofia, 2024)
Productive waste is described by Jean Baudrillard as one of the most striking reactions to the high internal operating costs of consumer society. In order to sustain growth, this kind of society must integrate into its production processes some calculated disadvantages that are not based solely on consumption, but on the destruction of wide arrays of goods, which are thrown away prematurely to be bought again and again. Understanding productive waste is crucial to grasp the interplay between economic growth, consumerism, and environmental degradation, as it accelerates the commodification of nature through new patterns of destruction, like psychological and planned obsolescence. In this regard, the aim of the present paper is to examine productive waste in relation to violent symbolic destructions called “potlatches” in the interest of highlighting the risk of giving rise to what Marcel Mauss describes as the immense non-repayable potlatch, that is, an unequaled waste, that of the Earth.